Detection of Diatomic Molecules in the Dust Forming Nova V2676 Oph - M. Nagashima; A. Arai; T. Kajikawa; H. Kawakita; E. Kitao; T. Arasaki; G. Taguchi; Y. Ikeda (Acta Polytechnica CTU Proceedings)
Novae are generally considered to be hot astronomical objects and show effective temperatures up to 10,000 K or higher at their visual maximum. But, it is theoretically predicted that the outer envelope of the nova outflow can become cool enough to form molecules that would be dissociated at high temperatures. We detected strong absorption bands of C2 and CN radicals in the optical spectrum of Nova V2676 Oph, a very slow nova with dust formation. This is the first report of the detection of C2 and the second one of CN in novae during outburst. Although such simple molecules are predicted to form in the envelope of the outflow based on previous studies, there are few reports of their detection. In the case of V2676 Oph, the presence of the molecular envelope is considered to be very transient, lasting several days only.